Heat transfer by seepage in sand - Ghafoori, Yaser (Acta hydrotechnica, 2021)
Heat transfer within the soil is a complex process in the presence of seepage flow. In such conditions, the soil%s thermal behavior is influenced by the thermal and hydraulic properties of the medium as well as the initial conditions and boundary conditions to which the medium is subjected. This paper presents the experimental and numerical studies of heat transfer within the sand subjected to the seepage flow. It focuses on the influence of saturated hydraulic conductivity and the porosity of medium on the heat transfer process. The temperature distribution within the sand was monitored by the optical fiber Distributed Temperature Sensor (DTS). The experiment was performed on three types of silica-dominated sands with different saturated hydraulic conductivities and different Soil Water Characteristic Curve (SWCC). In addition to the experimental study, a coupled hydrothermal numerical model was designed in FEFLOW software and validated by comparing its results with the experimental measurements. To determine the influence of porosity and saturated hydraulic conductivity on heat transfer, we analyzed the numerical models for different values of porosity and saturated hydraulic conductivity. The numerical and experimental studies showed that the thermal velocity is higher in sand with higher saturated hydraulic conductivity and temperature declination occurs more quickly due to the heat convection process. Saturated sand with larger porosity has an overall higher heat capacity, wherefore the temperature declination started later in the measuring points but dropped down lower close to the temperature of the upstream water.
Keywords: heat transfer; koeficient prepustnosti; porosity; poroznost; precejanje; prenos toplote; saturated hydraulic conductivity; temperature; temperature, seepage